Organização do trabalho, gestão neoliberal e sofrimento psíquico: vivências subjetivas do psicólogo no trabalho na Atenção Básica em Saúde na pandemia de covid-19. - Sousa, Taciana Alves de (2023)
The general purpose of this research is to analyze the work organization (WO) of primary healthcare psychologists, during the Covid-19 pandemic, seeking to describe subjective perceptions about their experiences at work, as well as the relationships of pleasure and suffering at work. We seek to establish a dialogue at the interface of health, work, and subjectivity, based on data obtained through socio-demographic questionnaires, semistructured individual interviews and focus groups, carried out with workers in a sector of a city in Minas Gerais, having devices for analyzing the articulation subject and society in the field of Work-Related Mental Health and recovering the precepts of content analysis, according to Laurence Bardin and Maria Cecília de Souza Minayo. The material was referred to the theoretical category of psychological suffering by Christophe Dejours and mental exhaustion by Edith Seligmann-Silva. The analysis of the organization of work showed that primary care psychologists are subjected to the neoliberal model of management by targets and precarious working conditions, exposed to mental health risks that lead to wear of subjectivity and pathogenic suffering, which have been intensified by the pandemic peak moments. The work appears strongly marked by the issue of survival, as well as it has the meaning of suffering, despite feeling useful and experiencing pleasure from the recognition of their work by the team and patients, as well as being emotionally connected to work, which makes it a source of sublimation, pleasure, and health. The findings of this study can contribute to discussions about the mental suffering of psychologists in PC work, seeking to create measures and actions aimed at preventing health in this category.